2020
DOI: 10.1297/cpe.29.159
|View full text |Cite
|
Sign up to set email alerts
|

The long-term safety and effectiveness of growth hormone treatment in Japanese children with short stature born small for gestational age

Abstract: . This study aimed to characterize the safety and effectiveness of GH treatments, in usual clinical practice, in children with short stature born small for gestational age (SGA). This was a multicenter, open-label, non-interventional study ( NCT01110928 ) conducted at 150 sites in Japan (2009–2018). The primary objective was to assess the type and frequency of serious adverse drug reactions (SADRs) associated with long-term GH use. Overall, 452 naïve and 46 non-naïve (previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
2
12
0
5
Order By: Relevance
“…In our study, the CA-BA was high, and the vast majority of children did not equalise bone age with calendar age. In their analysis, Horikawa et al [ 28 ] found no significant progression of bone age to calendar age during long-term follow-up, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the CA-BA was high, and the vast majority of children did not equalise bone age with calendar age. In their analysis, Horikawa et al [ 28 ] found no significant progression of bone age to calendar age during long-term follow-up, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…The treatment of choice for children with short stature and the aforementioned conditions is GH therapy, which requires long-term daily self-injection of recombinant human GH at home. GH therapy is expected to improve the future quality of life (QoL) of children ( 3 , 4 , 5 ) by ultimately helping them achieve a normal adult height. However, suboptimal medication adherence can impair the long-term clinical effectiveness of GH therapy, thereby resulting in a shorter final adult height ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the mean height gain was 1.42 SDS for 3 years of GH treatment in short children born SGA. Several studies have reported that GH treatment in SGA children without catch-up growth increased height velocity and improves adult height [ 17 20 ]. A meta-analysis identified four randomized controlled trials on near adult height in short children with SGA who received GH treatment [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the four trials, the overall mean height gain was 1.5 SDS in GH treated versus 0.25 SDS in untreated SGA children, similar to our results. Recently, Horikawa et al [ 17 ] reported that mean height gain was 1.80 SDS from the start to the end of 5 years of GH treatment. Rapaport et al [ 22 ] also reported that SGA children who received GH treatment for 3 years achieved an increase of 0.8 height SDS, and the mean height gain was not different between children with SGA and those with GHD.…”
Section: Discussionmentioning
confidence: 99%